Progress of Geodynamics Projects in Pakistan - Shah, S.M.I. (Journal of Himalayan Earth Sciences, 1980)
Pakistan occupies critically material position in the evaluation of Geodynamics of "Alpine-Himalayans Region". This fact is being realized by national and international workers engaged in this region. This being the case, Pakistani scientists have only recently started making serious efforts towards this direction. Nevertheless, the programmes recently initiated by the Geological Survey of Pakistan for geological and geophysical investigations in collaboration with the foreign geological/geophysical organizations are contributing materially in the development of this subject in the country. As such Pakistan has just entered into meaningful understanding of geodynamics. Some of these programmes are specifically oriented to resolve the stratigraphic issues and structural framework in the northern and western regions of Pakistan which may ultimately be most helpful in the synthesis of Himalayan geology; while other projects of geophysical investigations are directly or indirectly related to the study of tectonic framework of Pakistan. The projects arc briefly described below.